Kritik Identitas dalam Cerpen Bali Karya Putu Wijaya dan Cerpen Majogjag Karya Djelantik Santha - Komang Wahyu Rustiani; I Gst Md Swastya Dharma Pradnyan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Short story is a medium of writers to articulate appreciation even critique toward social problems happen. Even though the story used narrative style of cross languages, the writers background still appeared inside the language meaning in every scheme plot of the story. Sociological aspect plays the role toward writers psychology through the language sign system in creating the short story. There are two Balinese writers, both are Putu Wijaya and Djelantik Santha with their short stories Bali and Majogjag. Both writers Psychology aspect was noticeably in their stories. Each writer has different style as critic about Bali condition. Putu Wijaya as a man of Bali talks about Bali condition from the outside of Bali Island. Djelantik Santha, on the other side, as a man of Bali talks about social problems from the inside of Bali Island. This paper, certainly, is interesting to discuss since present two Balinese writers with multiinterpretation paradigm toward Balinese people. Discussing about identity, recently, is one of central issue in the context of globalization. It is also become one of important discourse in the short story Bali and Majogjag. There was reformulation about identity degradation of Bali figure in their local culture identity. There was also reconstruction based on modification and identity changes they faced. The discussion of this paper reveals that language was not obstruction in creating literary works such short story, also the sociology aspect of writers in the process of social identity modification, rather the way of reformulation the characters in the short story used hyper semiotic perspective. Keywords: identity, Bali, Majogjag, Hyper semiotic